Material Nonlinear Analysis of Plane Structures Made of Cement Based Composite Materials Using the ANSYS System - Pencik, J. (Engineering Transactions, 2004)
At present, it is possible to carry out a structure analysis using various calculation systems based mainly on the Finite Element Method (FEM). These systems mostly include finite elements, which can be used for geometrical and material nonlinear analysis of civil-engineering structures. Most of these elements are derived and used especially for the analysis of steel structures. For the analysis of structures made of cement based composite materials are developed and special elements are used. The article describes the methods of analysis of structures made of cement based composite materials with respect to material non-linearity. The ANSYS analysis system is further described in the article and the beam element implemented in this system. The beam element detailed derivation, including the presentation of material models that can be used for an analysis with this element is presented. Some numerical examples are shown at the end of the article.